INTERNAL CONTROL AND THE INTERNAL AUDITOR. - Garbade, William H. (The Accounting Review, 1944)
Abstract The article highlights the role and function of internal auditors. The author discusses fundamental factors which have caused industry to promote internal auditing to a key position in the general scheme of internal control. During 1940s, various management aspects were handled by different employees of the firm. Industrial management adopted these and many other new techniques to combat certain basic shortcomings in big business enterprise. With its origin in the accounting field, internal auditing derives its distinctive position in the sphere of managerial control from a series of peculiar characteristics which are not common to other staff departments within the organization or to public accounting staffs. In other words, these qualities make internal auditing a tool for the management in establishing and maintaining enlightened internal control. The first of these inherent characteristics is prejudice, partiality, bias, or loyalty. Compared with the public accountant, the internal auditor is partial toward the company under audit because his client is his employer.